Penerapan Metode Material Requirement Planning (MRP) Dalam Perencanaan Persediaan Kopi - Khairani, Wiwin; Epi, Yus (TIN: Terapan Informatika Nusantara, 2023)
Material Requirement Planning (MRP) is a method used to plan raw material inventory. The aim of this research is to analyze the MRP method which is suitable for planning the supply of raw materials for Sanger Coffee and Americano Coffee products at Serayu Kopi Medan. The lotting techniques used in this research are the Lot For Lot (LFL) method and the Period Order Quantity (POQ) method. Based on the results of the research that has been carried out, the most effective and efficient method applied at Serayu Kopi Medan is the POQ method. The LFL method produces inventory costs of IDR 660,000, while the POQ method can produce inventory costs of IDR 502,000. This means that using the POQ Serayu Kopi Medan method will save costs of IDR 158,000. Based on the results of the research and discussion, it can be concluded that from the Lot Sizing calculation results, the total inventory cost obtained using the Period Order Quantity (POQ) method is IDR 502,000, which is the most effective and efficient method to use because it can minimize ordering costs and holding costs so that the total costs incurred small when compared to the Lot for Lot (LFL) method with a total cost of IDR 660,000.